Exploring the Factors Contributing to Teacher Turnover in Private Secondary Schools in Lagos State, Nigeria - Gbesoevi, Emmanuel Semako; Potokri, Onoriode Collins; Adebayo, Mariam Adekemi; Mutiu, Olanrewaju Isiaka (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Recognising the growing concern over high turnover rates in the private education sector, this study investigated the factors contributing to teacher attrition in private secondary schools within Educational District V of Lagos State, Nigeria. A multistage sampling strategy combined with purposive sampling was employed, and structured questionnaires were used to collect data from 200 teachers across 20 privately owned secondary schools. The findings revealed that salary structure, school location, workload, and working conditions significantly influenced attrition. Specifically, inadequate compensation, excessive workload, and stressful working conditions increased teachers’ likelihood of quitting, whereas supportive professional environments and welfare provisions enhanced retention. The study concludes that reducing teacher turnover requires deliberate interventions by school administrators and policymakers. It recommends fostering supportive and less stressful work environments, prioritising professional development, improving welfare schemes, and addressing workload and remuneration challenges. Implementing these measures can promote teacher retention and stability, thereby strengthening the quality of education delivery in private secondary schools.